APPLICATION OF RUSSIAN TERMINOLOGY IN GEODESY AND CARTOGRAPHY AT TECHNICAL HIGHER EDUCATION INSTITUTIONS - Rakhimova Dilrabo Pulatovna (International Journal of Literature and Language Studies, 2026)
This study investigates the role and application of Russian terminology in geodesy and cartography education within technical higher education institutions. It analyzes the historical development of scientific terminology in post-Soviet academic systems and evaluates its current relevance in engineering education. The research focuses on the coexistence of Russian, national, and English terminology systems and their impact on teaching quality, academic communication, and professional training.